Improving adequacy of mechanical-mathematical model of rotor dynamics on the balancing machine - Oleg A. Polushkin; Oleg O. Polushkin; I. Masmoud Fofana (Advanced Engineering Research, 2016)
The work objective is to determine the conditions for improving the operating efficiency of the balancing equipment. The problem is to increase accuracy and to reduce labor intensity of the rotor balancing. A rotor model on the balancing machine considered according to the vibration theory as a dynamic system with two degrees of freedom forms the basis of the research. As a result of the investigations, first, the necessity of applying vector influence coefficient values of the rotor model unbalance in each of the correction planes on the vibrations of the rotor poles on the balancer is proved. Secondly, the technique of their experimental determination is presented. The results obtained can be used to create balancing equipment (balancing machines and balancing sets) of new generation. The study is the development of the modern theory and practice balancing aimed at improving the adequacy of the dynamic rotor model.